Genotypic Diversity and Virulence Traits of Streptococcus mutans Isolated from Carious Dentin after Partial Caries Removal and Sealing. (21st January 2014) - Damé-Teixeira, Nailê; Arthur, Rodrigo Alex; Parolo, Clarissa Cavalcanti Fatturi; Maltz, Marisa
Abstract : The aim of this study was to compare the genotypic diversity and virulence traits of Streptococcus mutans isolated from carious dentin before and after partial dentin caries removal (PDR) and sealing. Carious dentin samples were obtained three months before and after the PDR and cavity sealing. Up to seven isolates of each morphological type of S. mutans were selected and strain identity was confirmed using gtfB primer. Genotyping was performed by arbitrary primer-PCR (AP-PCR). Acidogenesis and acidurance of the genotypes were evaluated as virulence traits. A paired t -test and a Wilcoxon test were used to compare the virulence of genotypes. A total of 48 representative S. mutans isolates were genotyped (31 before and 17 after the sealing). At least one of the genotypes found before the sealing was also found on dentin after the sealing. The number of genotypes found before the sealing ranged from 2 to 3 and after the sealing from 1 to 2 genotypes. No difference was observed in the acidogenesis and acidurance between genotypes isolated before and after the sealing. In conclusion, genotypic diversity of S. mutans decreased after the PDR and sealing, but the virulence traits of S. mutans remained unchangeable.